Self‐ and cross‐citations in the Journal of Applied Behavior Analysis and the Journal of the Experimental Analysis of Behavior: 2004‐2018. Issue 4 (4th June 2019) - Mahoney, Amanda; Li, Anita; Curiel, Hugo; Plattner, Callie; Poling, Alan
Abstract : We examined self‐ and cross‐citations in the Journal of Applied Behavior Analysis ( JABA ) and the Journal of the Experimental Analysis of Behavior ( JEAB ) from 2004 through 2018. Mean annual levels of self‐citations for JABA and JEAB were 40.1% and 28.7%, respectively. Overall, 5.1% of JABA citations were JEAB articles, and 2.3% of JEAB citations were JABA articles. Although overall cross‐citation levels were relatively low, 28.7% of the JABA articles reviewed had at least one JEAB citation, and 27.5% of the JEAB articles reviewed had at least one JABA citation. Authors in both journals cited articles addressing the topics of matching and motivating operations. The extent to which the basic and applied sectors of behavior analysis interact depends on how the interaction is measured. Nonetheless, the degree of interaction is growing, which is a good thing for the discipline.